The Influence of Customer Service and Product Quality on Purchasing Decisions Motorcycle - Nurjanah, Nurjanah (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study aims to analyze the influence of customer service and product quality on purchasing decisions. Customer service and product quality are two crucial factors that influence customer satisfaction and loyalty, which ultimately impact purchasing decisions. This study uses a quantitative method with a survey approach to collect data from 125 respondents who are consumers of a well-known retail company in a big city. The instrument used in this study was a questionnaire to measure respondents' perceptions of customer service, product quality, and purchasing decisions. The collected data were analyzed using multiple linear regression to determine the relationship between the independent variables (customer service and product quality) and the dependent variable (purchase decisions). The results of the study indicate that both customer service and product quality have a positive and significant influence on purchasing decisions. Specifically, product quality has a more dominant influence than customer service in influencing purchasing decisions. This shows that although good customer service and product quality remain the main factors that encourage consumers to make purchases. This study provides practical implications for company management to pay more attention to and improve the quality of their products and continue to provide excellent customer service. Thus, companies can increase customer satisfaction and loyalty, which will ultimately increase sales and profits.